Is There Any Correlation Between Green Synthesis Parameters and the Properties of Obtained Selenium Nanoparticles? - Aleksandra Sentkowska; Julia Folcik; Jakub Szmytke; Anna Grudniak (Molecules)
Selenium nanoparticles (SeNPs) show enormous potential in biomedical applications. In recent years, green methods of their synthesis have become very popular. In this work, the influence of green synthesis conditions on the properties of the obtained nanoparticles was investigated. For this purpose, extracts of eight medicinal herbs were used, and the reaction was carried out with changing ratios of reagents and variable temperature. All obtained SeNPs were characterized by high stability, which is confirmed by the negative values of their zeta potential ranging from −11.8 to −29.4 mV. The highest correlation coefficient was determined between the size of the obtained SeNPs and the ratio of reagents used for the synthesis (the correlation coefficient is 0.681 for the synthesis carried out at room temperature and 0.914 for elevated temperature). In each case, the smallest nanoparticles were obtained from the synthesis carried out in a 1:1 reagent ratio. It was assessed that sometimes it is difficult to determine correlations between the results collected for all syntheses; therefore, the same correlations determined for specific herbs were also analyzed.